Effect of Waste-based Geopolymer on Asphalt Binder Properties - Saleh, Amani Ashraf Ahmed (AUC Knowledge Fountain, 2023)
Many problems are facing Egyptian asphalt pavements. It cannot be denied that frequent and severe pavement distresses are sometimes experienced in many locations all over the Egyptian roadway pavement network. These distresses may occur at the early stages of the pavement’s life. As a result, this contributes to an increase in the maintenance and repair expenses induced on the government. Asphalt binder modifications have become necessary to overcome the issues of Egyptian Pavements. This work evaluates the physical and rheological behavior of incorporated waste-based geopolymers in asphalt binders. Two geopolymer types Fly Ash (FA) and Metakaolin-Silica Fume (MK-SF) were prepared in the lab and replaced the binder with 4, 8, and 12% by weight of the binder. The effect of geopolymer type, composition, and curing time on binder behavior are the three main parameters under investigation in this study. The scope of the study involved testing the modified binder for a period of twelve weeks to assess the effect of curing time within the binder on its behavior. The geopolymer-modified samples were thoroughly characterized using the Superpave grading system once every four weeks. The viscosity levels of the modified binder were determined using the Rotational Viscometer test. The storage stability test was also conducted to determine if physical separation took place when the modified binder was stored. Results indicated an enhancement in the performance of both FA and MK-SF geopolymer-modified asphalt (GMA). The optimum geopolymer-modified asphalt was 12% Fly Ash Geopolymer modified binder (FA GMA) having a performance grade (PG) of 76-28 followed by the 4% Metakaolin-silica fume geopolymer modified binder (MK-SF GMA) having a PG 70-28 compared to the virgin (control) binder with PG 58-22. Viscosity levels increased with increasing the percentage of the geopolymers and met the Superpave specification requirements which means that the produced GMA has satisfactory workability levels. Storage stability of all samples did not exceed a separation index of 15% indicating that physical separation was not significant and the geopolymer is well dispersed within the binder. The curing time of the geopolymer inside the asphalt binder has a tangible effect on the produced GMA in terms of both rutting and thermal cracking. This study provides insight into how modified asphalt pavements could behave under Egyptian climatic conditions. All the results indicate that the use of geopolymer as an asphalt binder modifier is a new and sustainable way that may enhance the performance of pavements and extend their service life. Consequently, this would lead to a lower frequency of road repairs and would ultimately reduce operational costs. Furthermore, geopolymers are green materials that do not negatively contribute to the environment. Partial replacement of asphalt binders may alleviate the negative impacts on the environment.